Systematic Review and Meta-Analysis of Randomised, Other-than-Placebo Controlled, Trials of Non-Individualised Homeopathic Treatment - Mathie, Robert T.; Fok, Yvonne Y.Y.; Viksveen, Petter; To, Aaron K.L.; Davidson, Jonathan R.T. (Homeopathy, 2019)
Introduction This study focuses on randomised controlled trials (RCTs) of non-individualised homeopathic treatment (NIHT) in which the control (comparator) group was other than placebo (OTP).Objectives To determine the comparative effectiveness of NIHT on health-related outcomes in adults and children for any given condition that has been the subject of at least one OTP-controlled trial. For each study, to assess its risk of bias and to determine whether its study attitude was predominantly ‘pragmatic’ or ‘explanatory’.Methods Systematic review. For each eligible trial, published in the peer-reviewed literature up to the end of 2016, we assessed its risk of bias (internal validity) using the seven-domain Cochrane tool, and its relative pragmatic or explanatory attitude (external validity) using the 10-domain PRECIS tool. We grouped RCTs by whether these examined IHT as alternative treatment (study design 1a), adjunctively with another intervention (design 1b), or compared with no intervention (design 2). RCTs were sub-categorised as superiority trials or equivalence/non-inferiority trials. For each RCT, we designated a single ‘main outcome measure’ to use in meta-analysis: ‘effect size’ was reported as odds ratio (OR; values > 1 favouring homeopathy) or standardised mean difference (SMD; values < 0 favouring homeopathy).Results Seventeen RCTs, representing 15 different medical conditions, were eligible for study. Three of the trials were more pragmatic than explanatory, two were more explanatory than pragmatic, and 12 were equally pragmatic and explanatory. Fourteen trials were rated ‘high risk of bias’ overall; the other three trials were rated ‘uncertain risk of bias’ overall. Ten trials had data that were extractable for analysis. Significant heterogeneity undermined the planned meta-analyses or their meaningful interpretation. For the three equivalence or non-inferiority trials with extractable data, the small, non-significant, pooled effect size (SMD = 0.08; p = 0.46) was consistent with a conclusion that NIHT did not differ from treatment by a comparator (Ginkgo biloba or betahistine) for vertigo or (cromolyn sodium) for seasonal allergic rhinitis.Conclusions The current data preclude a decisive conclusion about the comparative effectiveness of NIHT. Generalisability of findings is restricted by the limited external validity identified overall. The highest intrinsic quality was observed in the equivalence and non-inferiority trials of NIHT.
Keywords: comparative effectiveness; explanatory trial; non-individualised homeopathic treatment; meta-analysis; pragmatic trial; randomised controlled trial; risk of bias; systematic review